Immunoglobulin binding proteins in ticks - Wang, H (1995)
Host (guinea pig) IgG was detected in haemolymph, salivary gland extracts (SGE) and saliva of female Rhipicephalus appendiculatus ticks. ELISA data indicated that ticks excrete host IgG via salivary glands during feeding. IgG binding proteins (IGBP) in salivary glands were detected by SDS-PAGE following extraction using an IgG-agarose column. IGBPs were also detected in SGEs of Amblyomma variegatum, and Ixodes hexagonus ticks. The IGBPs vary in sizes among different tick species. In R appendiculatus, the molecular weights of IGBPs in haemolymph differ from those in salivary glands. There are abundant IGBPs in salivary glands of male feeding R. appendiculatus ticks. Three of them (IGBPMA, -MB, and -MC) were isolated, N- terminal sequenced, and used to raise antisera. Western blotting data showed that all of them are male specific proteins. Their appearance was independent of copulation. IGBPMA only bound IgG of guinea pig, on which the ticks are maintained, whereas IGBPMC bound IgGs of guinea pig, bovine, and human origin. IGBPMA (29 kD) has a 30 kD precursor protein that can also bind to IgG. From a λ-Zap library of male R. appendiculatus ticks (produced by Guido Paesen), cDNAs of IGBPMA, -MB, and -MC were cloned and sequenced. Based on the sequencing data, all three IGBPs are novel proteins. A large open reading frame was detected preceding the N-terminus of IGBPMA. IGBPMB and -MC are related proteins. Both of them are glycoproteins, but only IGBPMC has a signal sequence at the N-terminus, suggesting that IGBPMC could be a secreted product. Recombinant IGBPMB and -MC were expressed using a glutathione S-transferase (GST) gene fusion system and a baculovirus expression system. None of the recombinant proteins was soluble. Recombinant IGBPMB and -MC were used to immunise guinea pigs for testing the anti- tick feeding effect. Male ticks fed on the immunized guinea pigs did not show detectable adverse effects during feeding. The female ticks fed on IGBPMB-immunized guinea pigs also engorged normally. However, the engorgement of female ticks fed on IGBPMC immunized guinea pigs was delayed (P<0.05, Student's t-Test, vs control). Furthermore, engorged weights of the female ticks were reduced (76 % of control, P<0.05) when the females co-fed on a naive guinea pig with the male ticks that were inoculated with anti-IGBPMC serum in situ. Thus, female tick engorgement was impaired when Jhe IGBPMC of the co-feeding male ticks was blocked by antiserum. Even though the function of IGBPMC is not clear, this IgG binding protein produced by male ticks could play a role in helping the co-feeding female ticks to obtain a successful blood meal. Host immunoglobulins can pass through tick midgut into the haemolymph with then- antibody activities intact. The data presented in this thesis indicate that ticks may have a mechanism, involving the IGBPs, that can deal with potentially harmful proteins (e.g., IgG) from the host. This undefined mechanism could be a part of the tick self-defence system which has not been previously mentioned by researchers. As IgG Fc receptors are reported to be required for the vertebrate host to develop an anti-tick resistance, IgG molecules and the IGBPs that are secreted by ticks via salivary glands into the feeding sites, could also play a role in minimising the host rejection response against tick feeding.